Selling Assets: Are Sellers Better Off with Strong Buyers? - Marquez, Robert; Singh, Rajdeep (Management Science, 2023)
When do sellers benefit from the presence of a strong buyer? In a second price auction with independent private values and entry costs for buyers, we allow for one buyer to be stochastically “strong.” We show that, when buyers make positive net profits, seller revenue is higher with a stronger buyer. In contrast, when competition is endogenous so that all buyers other than the strong buyer break even, seller revenue is always lower in the presence of a strong buyer. We also study seller actions such as providing buyer subsidies, setting reserve prices, securing multiple strong buyers, bundling assets, and optimally choosing the time of sale that might alleviate the fall in revenue. This paper was accepted by Will Cong, Finance. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2023.4938 .